Bioelectrochemical enhancement of anaerobic methanogenesis for high organic load rate wastewater treatment in a up-flow anaerobic sludge blanket (UASB) reactor - Zhao, Zhiqiang (Nature Publishing Group, 2014)
A coupling process of anaerobic methanogenesis and electromethanogenesis was proposed to treat high organic load rate (OLR) wastewater. During the start-up stage, acetate removal efficiency of the electric-biological reactor (R1) reached the maximization about 19 percentage points higher than that of the control anaerobic reactor without electrodes (R2), and CH(4) production rate of R1 also increased about 24.9% at the same time, while additional electric input was 1/1.17 of the extra obtained energy from methane. Coulombic efficiency and current recorded showed that anodic oxidation contributed a dominant part in degrading acetate when the metabolism of methanogens was low during the start-up stage. Along with prolonging operating time, aceticlastic methanogenesis gradually replaced anodic oxidation to become the main pathway of degrading acetate. When the methanogens were inhibited under the acidic conditions, anodic oxidation began to become the main pathway of acetate decomposition again, which ensured the reactor to maintain a stable performance. FISH analysis confirmed that the electric field imposed could enrich the H(2)/H(+)-utilizing methanogens around the cathode to help for reducing the acidity. This study demonstrated that an anaerobic digester with a pair of electrodes inserted to form a coupling system could enhance methanogenesis and reduce adverse impacts.